2014
DOI: 10.5812/hepatmon.9832
|View full text |Cite
|
Sign up to set email alerts
|

InSilico Identification and Conservation Analysis of B-cell and T-Cell Epitopes of Hepatitis C Virus 3a Genotype Enveloped Glycoprotein 2From Pakistan: A Step Towards Heterologous Vaccine Design

Abstract: Background:Hepatitis C virus (HCV) is known for the eminent global disease burden responsible for encumbering public health. Development of an effective vaccine is the major need of the day; however, several obstacles loom ahead of this objective. One of the major barriers is that as a RNA virus, it mutates rapidly resulting in high sequence divergence and several viral isolates in the world. Theglycoprotein 2 (gpE2) is the primary component of HCV envelope with direct interaction with the host cell surface re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…But this peptide had no high antigenicity score in the present study (29). In a similar study, Ikram et al confirmed that many epitopes from E2 protein are conserved in HCV 3a genotypes and HCV gpE2 is an ideal target for HCV vaccine design (30). In another study more probable and conserved T-and B-cell epitopes of E1 protein from HCV isolated in Pakistan were introduced as potential B-and T-cell epitopes that can raise the desired immune response against HCV (31).…”
Section: Discussionmentioning
confidence: 43%
“…But this peptide had no high antigenicity score in the present study (29). In a similar study, Ikram et al confirmed that many epitopes from E2 protein are conserved in HCV 3a genotypes and HCV gpE2 is an ideal target for HCV vaccine design (30). In another study more probable and conserved T-and B-cell epitopes of E1 protein from HCV isolated in Pakistan were introduced as potential B-and T-cell epitopes that can raise the desired immune response against HCV (31).…”
Section: Discussionmentioning
confidence: 43%
“…Most of the prediction of epitopes are based on E2 sequence (Ikram, Anjum, & Tahir, 2014) not for the HCV [E1.E2] complex. Our result shows 18 sequential epitopes present in the sequence of [E1.E2] that is part of our model (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…To enhance the immunogenicity of CD8+ T-cell responses, a Th CD4+ epitope (HLA-DR) from NS3 (NS31248-1262) was also chosen. Since clearance of HCV infection is associated with early appearance of broad neutralizing antibody responses, a neutralizing B-cell epitope from E2 (E2412-426) conserved between genotypes of HCV was considered for incorporation into the set of epitopes ( 25 , 26 , 32 ).…”
Section: Methodsmentioning
confidence: 99%